Seaview Inn - Woods, Sherryl (Don MIlls, Ontario, Canada : Harlequin MIRA, 2013)
Hannah Matthews prides herself on being able to handle any crisis. But with her grandmother balking at going into a retirement home, her daughter unexpectedly pregnant and an old flame suddenly underfoot, Hannah is facing a few crises of her own. And being back home on Seaview Key is most definitely adding to the stress.
Originally published: 2008.
Keywords: Single mothers -- Fiction; Breast -- Cancer -- Patients -- Fiction; Pregnancy -- Fiction; Bed and breakfast accommodations -- Fiction; Florida Keys (Fla.) -- Fiction; Domestic fiction; Love stories